Indonesia Pengaruh gratis ongkos kirim dan price discount terhadap perilaku implusive buying gen z pad marketplace shopee (studi kasus mahasiswa uin sjech m.djamil djambek bukittinggi) - Vinalia (UNCANG : Journal of Sharia Banking and Islamic Finance, 2025)
Phenomenon of impulsive buying which has become a concern along with the rapid development of e-commerce and aggressive marketing strategies. This study uses a quantitative approach. Primary data were collected through questionnaires distributed to 96 respondents of UIN Sjech M. Djamil Djambek Bukittinggi students who actively use the Shopee application. The sampling technique used was purposive sampling. Data analysis was carried out using descriptive statistical tests, validity tests, reliability tests, classical assumption tests (normality, multicollinearity, heteroscedasticity, autocorrelation), linear regression analysis, as well as partial (t-test) and simultaneous (F-test) hypothesis tests, and coefficient of determination. The results of this study indicate that the free shipping variable does not have a partial effect on impulsive buying behavior. This is evidenced by the t-count value of 1.293 and a significance value of 0.199≥ 0.05, and t-count ≤t-table (1.293 ≤1, 985). The effective contribution of free shipping to impulsive buying is 6% and the relative contribution is 17%. Then the price discount variable has a partial significant effect on impulsive buying behavior. This is evidenced by the t-count value of 4.694 and a significance value of 0.000 ≤0.05, and t-count≥ t-table (4.694≥ 1.985), the effective contribution of price discount to impulsive buying behavior is 28%, and the Relative Contribution is 83%. Then the F test shows that free shipping, price discount, have a positive and significant effect simultaneously on Gen Z impulsive buying behavior. This is evidenced by the F-count value of 23.602 and a significance value of 0.000 ≤0.05, and F-count≥ F-table (23.602≥ 3.09). The ability of the two independent variables to explain the dependent variable (impulsive buying) is 33.7% (Adjusted R Square = 0.337), while the remaining 66.3% is explained by other variables outside this research model.